The Immigration and Colonization Council and its Actions in the Brazilian Immigrantion Policy (1938-1945) - Debastiani, Jesiane [UNESP] (My University, 2022)
When Getúlio Vargas assumed the presidency of the country in 1930, several centralizing measures were initiated, and these actions also affected the immigration policy, which became restrictive and selective. To deal with issues involving immigration and colonization, Vargas created it at the Council for Immigration and Colonization (CIC) in 1938, months after the establishment of the Estado Novo. The objective of this article is to analyze the creation of the CIC, to point out the composition of the Council, that is, its members, its actions and debates regarding the immigration and migration issue, mainly of northeastern people from 1938 to 1945. Header Note that despite the great importance of the Council for immigration, it has been little analyzed by historiography. To accomplish the objectives proposed in this article, we will use the periodical published by the Council, the Revista de Imigração e Colonização (RIC).
O CONSELHO DE IMIGRAÇÃO E COLONIZAÇÃO E SUAS AÇÕES NA POLÍTICA IMIGRATÓRIA BRASILEIRA (1938-1945)
Keywords: Immigration; Immigration and Colonization Council; Vargas government